2022
DOI: 10.1002/jum.16056
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve of USgHIFU Ablation for Uterine Fibroids: A Multi‐Center Prospective Study

Abstract: Objectives To verify the stability of high‐intensity focused ultrasound (HIFU) technology and the feasibility of training programs with learning curve cumulative summation (LC‐CUSUM). Methods A total of 12 physicians and 720 cases were equally assigned to the learning group and the control group, with 6 physicians and 360 cases per group. The learning group was treated by physicians without HIFU experience and the control group was treated by experienced physicians. Nonperfused volume (NPV) ratio was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The long-term outcome of USgHIFU is comparable to that of myomectomy. Liu et al (21) showed that an NPVR of 70%…”
Section: Discussionmentioning
confidence: 99%
“…The long-term outcome of USgHIFU is comparable to that of myomectomy. Liu et al (21) showed that an NPVR of 70%…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the long-term re-intervention rate was similar between the group with NPVR of 80–89% and the group with NPVR ≥ 90%, and the difference was not statistically significant ( P = 0.880). Liu et al [ 25 ] showed that an NPVR of 70% was considered an appropriate indicator of training quality. Gong et al [ 26 ] showed that experienced doctors can achieve 80% NPVR when treating uterine fibroids, and even more than 90% of doctors have more clinical experience.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we did not try to use other NPVR values as prediction dividing lines for treatment success, only NPVR ≥ 80% was used in this study. Because measures to achieve 80% NPVR is technically feasible and have been proven to be highly associated with a clinical treatment success [ 3 , 4 , 38 ]. Finally, while patients at both institutions were treated with the same HIFU system, a potential biased limitation is that the treatment was performed by different doctors, which could influenced dosage delivery or the termination of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As an ablation technique, the efficacy of HIFU is closely related to the immediate postoperative non-perfused volume ratio (NPVR). A higher NPVR heralds a significant improvement in the patient’s symptoms, and an NPVR of over 80% is considered as an indicator of therapeutic success in recent studies [ 3 , 4 ]. However, not all patients can benefit from this treatment because of several limitations, such as high cellularity and high vascularity in the fibroids, which will hinder the deposition of ultrasonic energy and make ablation outcomes unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation